Better safe than sorry? Frequent attendance in a hospital emergency department: an exploratory study. Issue 1 (February 2018) - Daniels, Jo; Osborn, Mike; Davis, Cara
Introduction: Pain accounts for the majority of attendances to the Emergency Department (ED), with insufficient alleviation of symptoms resulting in repeated attendance. People who frequently attend the ED are typically considered to be psychologically and socially vulnerable in addition to experiencing health difficulties. This service development study was commissioned to identify the defining characteristics and unmet needs of frequent attenders (FAs) in a UK acute district general hospital ED, with a view to developing strategies to meet the needs of this group. Methods: A mixed-methods multi-pronged exploratory approach was used, involving staff interviews, focus groups, business data and case note analysis. Results: Findings reflect an absence of a coherent approach to meeting the needs of FAs in the ED, especially those experiencing pain. FAs to this ED tend to be vulnerable, complex and report significant worry and anxiety. Elevated anxiety on the part of the patient may be contributing to a 'better safe than sorry' culture within the ED and is reported to bear some influence on the clinical decision-making process. Discussion: It is recommended that a systemic approach is taken to improve the quality and accessibility of individualised care plans, provision of patient education, psychological care and implementation of policies and procedures. Change on an organisational level is likely to improve working culture, staff satisfaction and staff relationships with this vulnerable group of patients. A structured care pathway and supportive changes are likely to lead to economic benefits. Further research should build on findings to implement and test the efficacy of these interventions.